Sexual Identity, Earnings, and Labour Market Dynamics: New Evidence from Longitudinal Data in Australia - Joseph J. Sabia; Mark Wooden (Institute for the Study of Labor (IZA), 2015)
Using newly collected data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey, this study presents new estimates of the earnings effects of sexual orientation in Australia and offers the first empirical investigation of the labour market trajectories of lesbian/gay/bisexual individuals. Our results show that gay males are: (i) less likely to be continuously employed than their heterosexual counterparts, and (ii) face an earnings penalty of approximately 20 percent, driven, in part, by a longer-run earnings growth penalty relative to heterosexuals. Individual fixed effects estimates show that males entering into same-sex partnerships experience earnings declines relative to those entering into opposite-sex partnerships. For lesbians, we find evidence of an earnings premium, explained largely by increased labour supply on the intensive margin and, to a lesser extent, greater earnings growth over time.
Keywords: J31; J71; 330; sexual orientation; labour market dynamics; earnings trajectories; HILDA Survey